Kindergarten-based obesity prevention trial based on self-regulation strategy: study protocol of the Wuhan preschoolers’ healthy start project - Dong, Wenli; Wang, Yimin; Xu, Ke; Wang, Miyuan; Xia, Wenqi; Chen, Fengyan; Tuerxun, Paiziyeti; Jiang, Yanfen; Wei, Mengna; Zhou, Jiameng; Zhang, Jianduan (Frontiers in Pediatrics, 2025)
BackgroundChildhood obesity has surged in China, with preschool years being a critical window for intervention. Despite this, evidence-based randomized trials remain scarce, and traditional prevention strategies focusing on knowledge dissemination show limited long-term efficacy. The Wuhan Preschool Healthy Start (WPHS) project addresses this gap through a kindergarten-based trial integrating self-regulation strategies with energy balance-related behavior (EBRB) interventions.MethodsThis stratified randomized controlled trial enrolls children from 26 Wuhan kindergartens (13 intervention, 13 control) over 18 months. The multicomponent intervention targets diet, physical activity, sleep, sedentary behavior, and self-regulation, engaging children, families, and kindergarten environments. Control groups follow standard curricula. Primary outcome is the change in BMI z-score. Secondary outcomes assess behavioral factors (diet, sleep, activity), self-regulation skills, and other anthropometric indicators. Analyses adhere to intention-to-treat principles, using linear mixed models to evaluate intervention effects across strata while exploring potential effect modifiers including kindergarten level, child gender, and age.DiscussionThis intervention hypothesizes that the integrated components of health knowledge, behavior, and self-regulation will not only support the adoption of targeted health behaviors but also ensure their long-term maintenance. This unique approach makes the WPHS project an innovative and holistic initiative to prevent childhood obesity, providing valuable insights into public health strategies for this critical population. We anticipate that incorporating self-regulation training will improve the sustainability of behavior changes, addressing a key gaps in current preschool obesity interventions. Trial Registration NumberChinese Clinical Trial Registry ChiCTR2200058452.